Trophic State of Situ Patengan, Bandung Regency, West Java: Status Kesuburan Perairan Situ Patengan, Kabupaten Bandung, Jawa Barat - Ari Wahyuni; Aliati Iswantari; Ario Damar; Dwi Yuni Wulandari; Majariana Krisanti; Niken Tunjung Murti Pratiwi; Inna Puspa Ayu (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, IPB University, 2025)
Situ Patengan is designated as a Natural Tourism Park, offering recreational opportunities. However, human activities in the surrounding area can introduce both organic and inorganic materials, leading to changes in the lake’s trophic conditions. The trophic state level, which indicates the presence of nutrients, is used to evaluate the potential for the utilization of water bodies. The aim of this study was to assess the trophic state of Situ Patengan in Bandung Regency, West Java. Water samples were collected from the lake at four locations over three sampling periods. The trophic index (TRIX) method was applied to evaluate the lake’s trophic state. Total phosphate concentrations ranged from 0.041–0.187 mg/L, dissolved inorganic nitrogen concentrations varied between 0.20 and 0.64 mg/L, and chlorophyll-a levels ranged from 10.08 to 33.83 μg/L. According to the TRIX classification, the trophic state of Situ Patengan is considered eutrophic, with values ranging from 4.25 and 6.54. This information is valuable for predicting potential increases in trophic levels and guiding the sustainable management of Situ Patengan ecosystem.